2018
DOI: 10.1016/j.jfluidstructs.2017.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Control of flow separation around an airfoil at low Reynolds numbers using periodic surface morphing

Abstract: The paper investigates experimentally the low Reynolds number flow (Re c = 50, 000) around a model that approximates a NACA 4415 airfoil and the control of separation using periodic surface motion. Actuation is implemented by bonding two Macro Fiber Composite patches to the underside of the suction surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 50 publications
(72 reference statements)
4
14
0
Order By: Relevance
“…This behaviour could be due to possible energy transfer to the larger coherant structures by means of the periodic forcing. Similar effects were observed by Jones et al [20,21] where the actuation was found to cause a locked-on phenomenon causing the actuation frequency to dominate the spectra. This reduction could be translated into significant noise level reductions, yet the levels of PSD observed for the current amplitudes/ frequencies seems to be weaker than what is observed in literature.…”
Section: B Harmonically Morphing Tef Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…This behaviour could be due to possible energy transfer to the larger coherant structures by means of the periodic forcing. Similar effects were observed by Jones et al [20,21] where the actuation was found to cause a locked-on phenomenon causing the actuation frequency to dominate the spectra. This reduction could be translated into significant noise level reductions, yet the levels of PSD observed for the current amplitudes/ frequencies seems to be weaker than what is observed in literature.…”
Section: B Harmonically Morphing Tef Resultssupporting
confidence: 82%
“…Lee et al [19] carried out a similar study where a pitching NACA 0015 airfoil with a harmonically deflected flap was experimentally tested; the study showed evidence of a great impact on the CL and CM hysteresis while the leading-edge vortex formation and detachment was found to be unaffected by the flap motion. Jones et al [20,21] investigated both experimentally and numerically the use of periodic surface morphing for flow control purposes where the suction side of an airfoil was periodically morphed at various frequencies. Results showed that the actuation frequency dominated the spectra, causing the large coherent structures to add an extra momentum and effectively reduce the separation region, thereby reducing the drag.…”
Section: Introductionmentioning
confidence: 99%
“…2015; Jones et al. 2018) explained reattachment mechanism as follows. The oscillation amplifies the Kelvin–Helmholtz instability, which leads to the earlier rollup of the vortices and generation of a spanwise large coherent structure (LCS).…”
Section: Discussionmentioning
confidence: 99%
“…With the development of smart materials, surface actuators are becoming practicable as active flow control tools. DeMauro et al (2015) and Jones et al (2018) improved aerodynamic performance by producing a standing-wave oscillation on the suction side of an airfoil. Recently, travelling waves have been created experimentally on flexible structures using multiple piezoelectric actuators (Bani-Hani & Karami 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the efforts for advancement in aerodynamics has been focusing in shape optimization, where the key criteria are to reduce total drags with significant improvement in lift to drag ratio. Numerous studies have also been conducted by using boundary layer control like plasma actuator [3,4] and surface morphing [5] to delay the flow separation. Apart from that, an innovative design concept in morphing technology has gain much interest through the shape-changing ability for acquiring the best possible aerodynamic shape given the flight condition [6,7].…”
Section: Introductionmentioning
confidence: 99%